A hot-rolled composite phase 1860MPa grade stranded wire rod and its manufacturing method
Through the design of the C-SI-Mn-CR component design and the temperature quenching technology of online melting salt, the 1860MPA-grade steel twisted risk is high, and the high strength and plasticity matching and tissue uniformity control of the discs are achieved. It is suitable for high -efficiency production for 1860MPA graphics.
Patent Information
- Application Number
- CN202411536303.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The risk of breaking wires for 1860MPa grade steel strands is high during the drawing process, and it is difficult for the prior art to effectively control the formation of mesh carbides and martensite, resulting in a decrease in tissue uniformity and fluctuations in mechanical properties.
The hot-rolled reciprocating disk design of the C-SI-MN-CR component is designed. Through the temperature quenching technology such as online melting salt, the bar is controlled to quickly enter the pearl and light phase area from the high temperature oxytone state to inhibit the formation of mesh-shaped carbides, and and and of. After the temperature of the melting salt melting salt, the temperature recovered, promoted the formation of quenching shell -to -gene, regulated the compound tissue of the bars, and achieved high -intensity and plasticity matching.
It improves the uniformity of the tissue and the controllability of the compound tissue, reduces the risk of broken wire, realizes the effect of high -strength and plasticity, and is suitable for high -efficiency production of 1860MPA -class twisted.
Smart Images

Figure CN119020571B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and in particular relates to a hot-rolled complex phase 1860MPa grade stranded wire rod and a manufacturing method thereof. Background Art
[0002] As a typical representative product of steel strand, 1860MPa grade steel strand is widely used in mining, construction, railway and bridge systems. Steel strand is made of hot-rolled wire rod as the base material, and is made through pickling, multi-pass wire drawing, winding, unwinding, and rope braiding. The improvement of the base material wire rod specifications for strand is conducive to the application development of high-strength and lightweight strands, thus promoting the continuous increase in demand for large-size base material hot-rolled wire rod for 1860MPa grade steel strand. However, the base material specifications also lead to the difficulty of controlling abnormal tissues such as network carbides and martensite in the wire rod and the uniformity of the tissue, which leads to an increase in the risk of wire breakage during the wire drawing process. The existing 1860MPa grade steel strand wire rod generally adopts 82B composition, and is combined with the Stelmor air cooling line after rolling to produce 11~13mm fine lamellar pearlite steel wire rod. Therefore, the 1860MPa grade steel strand wire rod with larger manufacturing specifications, better strength and plasticity and uniformity of organization, lower material cost, and easy and efficient production still has the following technical difficulties:
[0003] C and Mn in the wire rod are elements that improve the strength of steel. The high content will aggravate the central segregation of the continuous casting billet and improve the hardenability of the wire rod. In the process of Stelmor controlled cooling after rolling, it is easy to form abnormal structures such as network carbides and hard-brittle martensite that deteriorate the plasticity and drawing properties of large-size high-carbon steel wire rods, resulting in a decrease in the uniformity of the wire rod structure and an increase in the fluctuation of mechanical properties, which will cause wire breakage in the subsequent deep drawing process. Therefore, in order to improve this problem, for example: Patent CN108004470B discloses a low-manganese high-carbon steel wire rod for high-strength steel strands and a preparation method, which adopts a C-Si-Mn-Cr composition design with reduced Mn content combined with an increase in the spinning temperature after rolling and Stelmor first fast and then slow cooling to obtain a wire rod with a troostite content ≥90%, narrowing the performance fluctuation range, but:
[0004] 1. Reducing the Mn content will lead to a greater loss of strength, and the area reduction rate needs to be increased to achieve the strength grade of the stranded wire. The plasticity loss is large during the process, which increases the risk of wire breakage. If alloy elements such as V and B are continued to be added to increase the strength of the wire rod, the material cost will increase.
[0005] 2. Although the precipitation of network cementite is suppressed by cooling with large air volume after spinning, the maximum cooling capacity of the Stelmore air cooling line is limited, generally only reaching 10℃ / s. The time for the wire rod to pass through the secondary cementite precipitation zone is still relatively long, and the problem of network carbide will still exist. At the same time, the increase in the fan air volume will further increase the uncontrollable influence of wind speed and wind temperature. Even if the packing density of the wire rod is reduced, there is still a large temperature difference between the wind-receiving side and the wind-receiving side of the wire rod, which makes some positions form hard and brittle bainite or martensite structure that is not conducive to drawing at a faster cooling rate. The temperature gradient from the edge to the core of the wire rod cross section is large, which makes the distribution of troostite content from the edge to the core have a large difference. In the process of continuous air cooling and temperature control, the precipitation of abnormal structure is uncontrollable, which affects the uniformity and plasticity of the wire rod structure, and further aggravates the risk of wire breakage during drawing.
[0006] 3. In order to improve the strength of the wire rod after reducing the Mn content as much as possible, although the wire drawing temperature is increased and the wire drawing temperature is slowed down after rapid cooling to extend the phase transformation time of the wire rod as much as possible, so as to refine the lamellar spacing and increase the content of sorbite with good drawing performance and strength in the organization, on the one hand, the slow cooling process of increasing the wire drawing temperature and combining with reducing the air volume of the fan will make the online time of the wire rod on the Stelmor cooling line longer, affecting the processing efficiency. On the other hand, the hardenability of the wire rod decreases after reducing the Mn content, and the maximum cooling capacity of the rapid cooling after rolling is limited, which will make the pearlite organization coarsening, making it difficult to obtain a sorbite organization with finer lamellar spacing, resulting in a certain strength loss. Even if the cooling rate during the phase transformation of the wire rod is further reduced, the minimum cooling capacity of the Stelmor air-cooled line is limited. The incubation time of the wire rod phase transformation is limited during the continuous cooling process, which will make the final troostite content not high enough and will also cause strength loss. At the same time, the coarser cementite lamellae of the wire rod will increase the difficulty of softening. After the troostite inoculation, the wire rod is already in a low temperature state and the thermal power is insufficient, which will make the obtained troostite or pearlite structure have higher organizational stress and dislocation density and greater resistance to plastic deformation. The precipitation and coarsening of Cr during the phase transformation process will also lose strength and plasticity, resulting in insufficient strength and plasticity of the wire rod, which will increase the risk of wire breakage during the wire drawing process. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a hot-rolled complex phase wire rod for 1860MPa grade stranded wire and a manufacturing method thereof, which can improve the uniformity of the wire rod structure, regulate the complex phase structure of the wire rod, achieve high strength and plasticity matching of the wire rod, and achieve efficient production. It is used for the manufacture of 1860MPa grade stranded wire and can reduce the risk of wire breakage during the wire drawing process.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for manufacturing a hot-rolled multi-phase 1860 MPa grade stranded wire rod, the manufacturing method comprising:
[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled complex phase wire rod, wherein the chemical composition and mass percentage of the hot-rolled complex phase wire rod include: C: 0.80%~0.84%, Si: 0.20%~0.40%, Mn: 0.20%~0.35%, Cr: 0.15%~0.25%, P≤0.014%, S≤0.014%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥895°C, it is subjected to an online molten salt isothermal quenching treatment, so that the wire rod first passes through a front-stage molten salt and is quenched at ≥39°C / s cooling rate, from the austenite state into the pearlite phase region, so that part of the austenite phase transformation to form a troostite-based organization, and then after the molten salt cooling in the latter stage, the residual austenite is promoted to transform into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and part of the cementite sheets are micro-spheroidized. Finally, after the roller strong slow cooling, the microstructure is made into a hot-rolled complex phase wire rod including 81% to 87% of tempered troostite by volume, 7% to 12% of tempered bainite by volume, and the rest is a complex phase organization composed of tempered ferrite and micro-spheroidized carbides.
[0011] The chemical composition and mass percentage design basis of the hot rolled multiphase wire rod include:
[0012] (1) Carbon: As a basic strengthening element in steel, C can improve the tensile strength of wire rod through solid solution strengthening. However, if the C content is too high, the central segregation, decarburization and precipitation tendency of network cementite in the solidification process of large-size high-carbon steel alloy will be aggravated, thereby reducing the uniformity of the same circle and the plasticity of the wire rod. Therefore, in order to take into account the high strength of 1860MPa grade stranded wire, reduce the difficulty of controlling the uniformity of the organization and consider the material cost, it is more conducive to refining the cementite sheet during online molten salt isothermal quenching to reduce the softening difficulty. The mass percentage of C is controlled to be 0.80%~0.84%.
[0013] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It can improve the strength of the wire rod through solid solution strengthening, which is beneficial to obtaining a finer troostite structure. At the same time, it can inhibit the coarsening of cementite and accelerate the diffusion rate of carbon, which is beneficial to promote the microspheroidization of some cementite sheets. However, too high silicon will promote C desolvation and prolong the phase transformation time, which is not conducive to rapid phase transformation and tempering during online molten salt isothermal quenching. Therefore, the mass percentage of Si is controlled to be 0.20%~0.40%.
[0014] (3) Manganese: Mn can be added as a deoxidizer during the steelmaking process. It can be dissolved in austenite to strengthen the matrix, increase the stability of austenite, improve the hardenability of wire rod, reduce the phase transformation temperature, and then form a troostite structure and a quenched bainite structure with fine interlayer spacing to improve the matrix strength. However, when the Mn content is too high, it will increase the central alloy element segregation of the steel billet, increase the risk of abnormal structure precipitation and material cost, and reduce the diffusion activity of carbon. It is not conducive to promoting the rapid tempering softening of troostite and quenched bainite and the micro-spheroidization of cementite sheets during isothermal tempering, thereby reducing the drawing performance of the wire rod. Therefore, in order to take into account the high strength-plasticity combination and uniformity of the hot-rolled complex phase wire rod and further reduce the material cost, a lower Mn content is selected, and the mass percentage of Mn is controlled to be 0.20%~0.35%.
[0015] (4) Chromium: Cr is a medium-strong carbide-forming element in high carbon steel. It can exist in cementite lamellae, improve the stability of austenite, prevent grain growth during rolling, and shift the continuous cooling transformation curve of steel to the right. At the same cooling rate, it can refine the spacing between troostite lamellae and promote the nucleation of quenched bainite, thereby making the proportion of tempered bainite easier to control and compensating for the strength loss by reducing the Mn content. However, high Cr content will aggravate segregation, and too low phase transformation temperature is not conducive to the rapid softening of troostite and quenched bainite. Therefore, the mass percentage of Cr is controlled to be 0.15%~0.25%.
[0016] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.014% and S is ≤ 0.014%.
[0017] The hot-rolled complex phase wire rod adopts C-Si-Mn-Cr composition design, with relatively lower Mn content and no precious alloy elements such as V and B, which can further reduce material cost and segregation effect, and appropriately adjust the peak precipitation temperature of troostite and quenched bainite to be lowered, so that the precipitation of network carbides is easier to control, the coarsening of cementite is inhibited, and the diffusion activity of carbon is increased, which provides favorable conditions for troostite with finer interlamellar spacing and controllable quenched bainite phase deformation nucleation and rapid tempering softening. On this basis, the manufacturing method selects a higher spinning temperature to ensure that the wire rod is in a high-temperature austenitized state, prevent the precipitation of network carbides in the spinning stage, and directly perform online molten salt strong quenching treatment after spinning:
[0018] 1. Compared with the existing Stelmore air-cooling line, the maximum cooling capacity is limited, which makes it difficult to control the network carbide and the pearlite lamella spacing is coarse. The wire rod can use the rapid heat exchange capacity of the molten salt after passing through the front section of the molten salt to increase the cooling rate of the wire rod. On the one hand, under the influence of reducing segregation, the network carbide precipitation interval of 700~800℃ is effectively reduced, which can effectively inhibit the formation of network carbides, improve the utilization value and strengthening effect of carbon elements, and avoid the adverse effects of network carbides on organizational uniformity and plasticity. On the other hand, the wire rod can quickly enter the pearlite phase region from the high-temperature austenite state, forming a larger temperature gradient and supercooling, promoting the transformation of a large amount of austenite structure to the troostite structure, and the troostite structure lamella spacing is finer, which is beneficial to improving the matrix strength and reducing the difficulty of isothermal tempering. At the same time, due to the rapid cooling of the wire rod, the online time of the wire rod can be effectively reduced, and there is no need to consider the adverse effects of high-temperature spinning on the online processing time as the Stelmore air-cooling line needs to do, thereby improving the processing efficiency.
[0019] 2. Compared with the existing Stelmor air-cooling line, the air-cooling intensity is increased, and the control difficulty of abnormal tissues such as martensite and tissue uniformity is increased. On the one hand, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for more uniform strong heat exchange, and there is no problem of windward side and leeward side, and the temperature gradient from the upper edge to the core of the wire rod section can be further reduced, and the temperature is more controllable. Therefore, the phase change of the wire rod is more uniform, which can avoid excessive cooling of some positions and the formation of martensite structure with degraded drawing performance. On the other hand, after the wire rod passes through the front section of the molten salt and undergoes the troostite phase transformation in the pearlite phase region, it is then subjected to the cooling isothermal treatment of the rear section of the molten salt, which can promote the rapid transformation of the untransformed residual austenite into the quenched bainite structure, and can make the small amount of precipitation of quenched bainite, which is conventionally regarded as an abnormal structure, more controllable, and thus higher than the matrix strength of the traditional troostite + ferrite, which can not only make up for the strength loss caused by reducing the Mn content, but also further improve the strength of the wire rod.
[0020] 3. Compared with the existing Stelmor air-cooled line, due to slow cooling and continuous cooling phase transformation, the online time is longer, the proportion of soft phase ferrite in the organization is still high, and the stress and dislocation density of the troostite organization are large, which affects the plasticity and drawing properties of the wire rod. On the one hand, the wire rod first passes through the front molten salt to form a troostite organization with finer interlamellar spacing, which provides favorable conditions for the rapid isothermal tempering and micro-spheroidization of cementite sheets in the rear molten salt. On the other hand, the wire rod is subjected to isothermal treatment of cooling in the rear molten salt instead of continuous cooling. The wire rod can be maintained at an appropriate temperature to promote the quenching bainite phase transformation. At the same time, it promotes the first formed troostite organization and the later formed quenching bainite organization. The bainite is isothermally tempered, and part of the cementite sheets are micro-spheroidized, so that the organizational stress and dislocation density of the bainite are reduced, the dislocation density of the quenched bainite is reduced and transformed into a strong and tough tempered bainite structure, and the micro-spheroidized carbides are evenly distributed on the plastic matrix, thereby improving the plasticity of the wire rod, and the quenched bainite is reasonably transformed and utilized. The isothermal tempering treatment makes the proportion of tempered bainite and tempered bainite more controllable. At the same time, this gradient cooling makes it unnecessary to increase the molten salt temperature in the later stage, and the control difficulty and production energy consumption are smaller. Cr will not coarsen at an excessively high molten salt temperature, which is detrimental to the strength and plasticity.
[0021] In the further roller intensive slow cooling process, the high temperature state of the wire rod after passing through the molten salt in the rear section can be continued, and the wire rod structure can be further toughened by reducing the cooling rate of the wire rod, thereby improving the tempering and softening effect of the wire rod, thereby realizing the complex phase structure control, high strength and plasticity matching and rapid production of the wire rod.
[0022] Due to the relatively high C content, the risk of decarburization of the steel billet in the furnace is reduced by further controlling the heating furnace parameters before rolling, and the uniform diffusion of the components is promoted. In a preferred embodiment, before rolling, the residual oxygen content in the heating furnace is controlled to be 1.3%~2.3%, the heating furnace soaking temperature is 1090~1120℃, and the furnace time is 2.5~4h.
[0023] After the billet is heated in the heating furnace, high-pressure descaling water is used to further remove the oxide scale on the billet surface to prevent the oxide scale from being rolled into the wire and affecting the surface quality of the wire. In a preferred embodiment, the descaling water pressure after the heating furnace is 14~17MPa.
[0024] Since the spinning temperature is relatively high, appropriate rolling temperature and reduction can be selected to promote dynamic recrystallization and grain refinement during the final rolling process to improve matrix strength and rolling efficiency. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1055~1085℃, the heavy-load finishing rolling reduction is 22%~28%, and the final rolling temperature is ≥915℃.
[0025] In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 500-520°C, and the processing time is 30-50s. The lower the molten salt temperature of the front-stage molten salt and the longer the processing time, the more troostite is formed and the finer the spacing between the troostite lamellae is, which is beneficial to the transformation of cementite sheets into microspheres, and will increase the proportion of tempered troostite in the organization, reduce the proportion of tempered bainite, and increase the plasticity of the matrix. However, if the molten salt temperature is too low and the processing time is too long, it will be unfavorable for the transformation of quenched bainite and will result in insufficient strength of the wire rod. On the contrary, if the molten salt temperature is higher and the processing time is shorter, the less troostite is formed and the spacing between the troostite lamellae is increased, so that more residual austenite can be left in the organization. It can transform into quenched bainite structure, so the proportion of tempered bainite in the structure is reduced, and the proportion of tempered bainite is increased, so that the matrix strength is increased. However, the molten salt temperature is too high, which is not conducive to the formation of bainite structure which is beneficial to drawing, and even forms pearlite or too much ferrite structure, which is not conducive to the subsequent isothermal tempering softening, resulting in matrix strength loss. The treatment time is too short, which is not conducive to the incubation of bainite, and will make the proportion of tempered bainite in the complex phase structure too high and the plasticity insufficient. Therefore, the molten salt temperature and treatment time of the front stage molten salt can be controlled to promote the transformation of most austenite structures to bainite with finer lamellar spacing, providing favorable conditions for the subsequent quenched bainite phase transformation and isothermal tempering.
[0026] Since the cooling rate of the wire rod from the spinning temperature to the pearlite phase region is fast and the temperature difference is large, the use of a higher molten salt circulation rate in the front stage can reduce the molten salt temperature rise and promote the uniform refinement of the interlamellar spacing of the formed troostite structure. In a preferred embodiment, the molten salt circulation rate of the front stage molten salt is 500~650t / h, and the molten salt temperature rise is ≤5℃.
[0027] In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 430-470°C, and the treatment time is 30-50s. The peak precipitation temperature of the quenched bainite and the isothermal tempering thermodynamics are taken into consideration in the rear-stage molten salt. The lower the molten salt temperature of the rear-stage molten salt and the longer the treatment time, the more conducive it is to promote the untransformed residual austenite in the structure after the front-stage molten salt, and quickly transform it into the quenched bainite structure, and then promote the toughening and softening of the structure under a longer isothermal tempering, so that part of the cementite sheets are micro-spheroidized, and the strength and plasticity of the matrix are improved. However, if the molten salt temperature is too low and the thermodynamics are insufficient, the isothermal tempering effect will be reduced, resulting in insufficient plasticity of the wire rod. If the treatment time is too long, there will be excessive softening and coarse precipitation of Cr. The risk of deterioration of strength and plasticity due to isothermal tempering is not conducive to efficient production; on the contrary, the higher the molten salt temperature and the shorter the treatment time, the more unfavorable it is for the rapid transformation of retained austenite into quenched bainite structure, resulting in a decrease in the proportion of tempered bainite and a decrease in matrix strength. If the molten salt temperature is too high, the proportion of tempered bainite will be too low, the wire rod will be easily over-softened, and the wire rod strength will be insufficient. If the treatment time is too short, the retained austenite will not be fully transformed, and the isothermal tempering softening and toughening effects will be reduced, which will easily lead to increased fluctuations in mechanical properties and increased brittleness of the wire rod. Therefore, the molten salt temperature and treatment time of the later molten salt can be further controlled to regulate the formation and toughening of the complex phase structure, taking into account efficient production, so as to regulate the matching of the strength and plasticity of the wire rod.
[0028] Since the temperature difference between the molten salt temperature of the wire rod and the molten salt temperature of the rear section is small, a smaller molten salt circulation rate can be selected. While controlling the molten salt temperature rise accuracy, the production energy consumption can be reduced. In a preferred embodiment, the molten salt circulation rate of the rear section molten salt is 300~450t / h, and the molten salt temperature rise is ≤3°C.
[0029] In a preferred embodiment, the roller strong slow cooling controls the wire rod to be cooled to below 300°C at a slow cooling rate of 0.1~0.3°C / s for coiling, and controls the wire rod passing through the rear molten salt to be slowly cooled at a lower slow cooling rate. The strong slow cooling treatment can continue the high temperature state of the wire rod after passing through the molten salt, promote further toughening of the wire rod structure, and improve the tempering softening effect of the wire rod.
[0030] In a preferred embodiment, the roller table strong slow cooling adopts a heat preservation cover to close the high-temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment, and the high-temperature gas above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller table, and the conveying roller table conveys the wire rod into the heat preservation cover. The high-temperature gas above the salt bath tank during the online molten salt isothermal quenching treatment can be recycled, which can maintain the hot atmosphere in the heat preservation cover to avoid the conveying speed being too low to affect the production rhythm, and save production energy consumption.
[0031] A hot-rolled complex phase wire rod for 1860 MPa grade stranded wire, wherein the hot-rolled complex phase wire rod is manufactured by any one of the above-mentioned methods for manufacturing the hot-rolled complex phase wire rod for 1860 MPa grade stranded wire.
[0032] The hot-rolled multiphase wire rod adopts the C-Si-Mn-Cr composition design, and the Mn content is lower, which can further reduce the material cost. At the same time, compared with the traditional stranded steel wire rod microstructure of pearlite / sodium+ferrite, the microstructure of the hot-rolled multiphase wire rod is mainly tempered sodium, a small part of tempered bainite, and the rest is tempered ferrite and micro-spheroidized carbide. The interlamellar spacing of sodium is finer than that of pearlite, and the drawing performance and strength are better. Sodium is transformed into tempered sodium after tempering, and part of the cementite sheets are micro-spheroidized and transformed into micro-spheroidized carbides. The organizational stress and dislocation density are further reduced, so that the plastic toughness can be improved. Compared with the quenched bainite which is conventionally regarded as an abnormal structure, the quenched bainite has higher strength and distortion, and the phase transformation and formation become more controllable. The quenched bainite is transformed into tempered bainite through isothermal tempering, and the dislocation density is reduced, so that a strong and tough structure is obtained, the proportion of tempered ferrite is reduced, and there is no abnormal martensite structure. Therefore, it can not only make up for the strength loss caused by reducing the Mn content, but also give full play to the strengthening effect of C and Cr, and use the complex phase structure to further improve the strength of the wire rod. It can also improve the plasticity of the wire rod through the organization control of the tempered state. It is more suitable for larger specifications of wire rods as the parent material to manufacture 1860MPa grade stranded wire, reducing the risk of wire breakage during drawing and braiding.
[0033] The finer the interlamellar spacing of tempered troostite, the more beneficial it is to improving the drawing performance of the matrix. However, if the interlamellar spacing of tempered troostite is too fine, the troostite phase transformation will affect the quenched bainite phase transformation more as the molten salt temperature of the previous stage molten salt decreases and time increases, which will cause the strength of the wire rod to decrease. In a preferred embodiment, the interlamellar spacing of the tempered troostite is 75~115nm.
[0034] In a preferred embodiment, the network carbide level of the hot-rolled multiphase wire rod is level 0, which can avoid the adverse effects of the network carbide wire rod microstructure uniformity, especially the plasticity of the wire rod, thereby reducing the risk of wire breakage during drawing.
[0035] In a preferred embodiment, the mechanical property difference of the hot-rolled multiphase wire rod is ≤30 MPa, the mechanical property fluctuation is smaller, and the risk of wire breakage during wire rod drawing can be reduced.
[0036] In a preferred embodiment, the diameter of the hot-rolled complex phase wire rod is 12~15mm, the tensile strength is 1290~1340MPa, the cross-sectional shrinkage rate is 41%~46%, and the wire rod diameter specification is relatively large. Due to the high reinforcement and lightweight of the stranded wire, the high tensile strength of the wire rod is beneficial to reducing the area reduction rate and the number of drawing passes, improving the production efficiency of the stranded wire, and avoiding the risk of wire breakage caused by excessive loss of wire rod plasticity during the process. The wire rod has a high plasticity, which is manifested as a higher cross-sectional shrinkage rate, which can further reduce the wire rod drawing deformation resistance and reduce the risk of wire breakage during wire rod drawing.
[0037] Compared with the prior art, the beneficial effects of the present invention are at least:
[0038] (1) Aiming at the current situation that the increase in the specifications of the 1860MPa grade steel strand base material leads to an increase in the difficulty of controlling the abnormal structures such as the network carbide and martensite of the wire rod and the uniformity of the structure, thereby increasing the risk of wire breakage during the wire drawing process, the manufacturing method of the present invention combines the C-Si-Mn-Cr chemical composition design with the online molten salt isothermal quenching technology, and controls the wire rod to quickly skip the network carbide interval and enter the pearlite phase region from the high-temperature austenite state through the front-stage molten salt, thereby inhibiting the formation of network carbides and forming a troostite structure with fine lamellar spacing. The wire rod is mainly composed of a structure with a molten salt as the main component, and then isothermal tempering is performed in the later stage to promote the rapid transformation of the untransformed residual austenite into the quenched bainite structure. At the same time, the isothermal tempering of the first formed troostite structure and the later formed quenched bainite is promoted, and micro-spheroidization of some cementite sheets is promoted to regulate the strength and plasticity matching of the wire rod. Finally, the strong and slow cooling on the roller promotes further toughening of the wire rod structure, which can not only improve the uniformity of the wire rod structure, regulate the multiphase structure of the wire rod, and achieve high strength and plasticity matching of the wire rod, but also enable efficient production and have good industrial adaptability.
[0039] (2) In view of the current situation that the mechanical properties of the 860MPa grade steel strand wire rod have large fluctuations and insufficient strength and plasticity, the hot-rolled multiphase wire rod of the present invention has a lower Mn content, which can further reduce the influence of segregation and material cost. The microstructure type is a composite structure composed of mostly tempered troostite, a small part of tempered bainite, and the rest of tempered ferrite and micro-spheroidized carbides, which can avoid the difficulty of suppressing abnormal structures such as network carbides and martensite and weakening their strengthening effect. It effectively utilizes the conventionally regarded as quenched bainite and transforms it into The strong and tough tempered bainite structure is used to improve the strength of the wire rod and make up for the strength loss caused by reducing the Mn content. The strength of the wire rod is further improved through the complex phase structure, and the plasticity of the wire rod is improved by using the structure regulation of the tempered state. The product tensile strength can reach 1290~1340MPa, the cross-sectional shrinkage rate is 41%~46%, the structure uniformity is better, the mechanical properties fluctuate less, and it is suitable as a base material for manufacturing 1860MPa grade stranded wire, reducing the risk of wire breakage during drawing and braiding, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0041] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0042] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0043] Figure 3It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0044] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0045] A preferred embodiment of the method for manufacturing the hot-rolled multiphase 1860MPa grade stranded wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled multiphase wire rod include: C: 0.82%, Si: 0.27%, Mn: 0.32%, Cr: 0.23%, P: 0.014%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal quenching → roller strong slow cooling → coiling, specifically:
[0046] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled plastically, and control the parameters of the heating furnace to reduce the risk of decarburization of the steel billet in the furnace. After the steel billet leaves the heating furnace, the surface oxide scale is removed by high-pressure descaling water and the billet is sent to the rolling line. The rolling line rolls the steel billet into a wire with a diameter specification of 14mm. The appropriate rolling temperature and reduction amount are selected to promote dynamic recrystallization and refine the grains during the final rolling process. Specifically: the heating furnace is heated up in sequence according to preheating, heating, and soaking, and the residual oxygen content in the heating furnace is controlled to be 1.8%. The furnace average heating temperature is 1100℃, the furnace time is 3.5h, the descaling water pressure after the heating furnace is 15MPa, the initial rolling temperature is 1060℃, the heavy-load finishing rolling reduction is 24%, and the final rolling temperature is 920℃; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The higher wire-spinning temperature ensures that the wire rods are in a high-temperature austenitized state and prevents the precipitation of network carbides, which provides favorable conditions for the subsequent formation of a larger degree of supercooling and thus refinement of the troostite lamellar spacing. Specifically: the wire-spinning temperature is controlled to be 900℃.
[0047] The online molten salt isothermal quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank, that is, it is subjected to the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 41°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to the pearlite phase area, inhibiting the formation of network carbides and causing part of the austenite phase to transform into a structure mainly composed of sorbite, and then conveyed by a roller through the second stage salt bath tank, that is, it is subjected to the rear stage molten salt treatment, and the cooling promotes The residual austenite is transformed into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and the micro-spheroidization of some cementite sheets is promoted to regulate the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 500°C, the processing time is 50s, the molten salt circulation volume is 650t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear-stage molten salt is 470°C, the processing time is 50s, the molten salt circulation volume is 300t / h, and the molten salt temperature rise is ≤3°C.
[0048] The roller strong slow cooling process adopts the insulation cover to close, and the high temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover, so as to promote the further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 280°C at a slow cooling rate of 0.3°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1As shown, its microstructure includes 87% tempered bainite by volume, 7% tempered bainite by volume, 1% tempered ferrite by volume and 5% micro-spheroidized carbide by volume, the interlamellar spacing of tempered bainite is 75nm, the grade of network carbide is 0, the difference in mechanical properties is 29MPa, the tensile strength is 1290MPa, and the section reduction rate is 46%.
[0049] Comparative Example 1:
[0050] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor strong air cooling → roller slow cooling, specifically: the heating furnace is controlled to have a soaking temperature of 1080°C, the furnace time is 4.5h, the initial rolling temperature is 1045°C, the final rolling temperature is 900°C, and the spinning temperature is 880°C; the Stelmor strong air cooling uses an air volume of 200,000 m per fan 3 / h, open 1~7# fans at 75%, cool the wire rod to 610℃ at a cooling rate of 6.7℃ / s, close the fan and cover the heat preservation cover on the roller for intensive slow cooling, cool the wire rod to 280℃ at a cooling rate of 0.8℃ / s, and obtain the hot-rolled wire rod after it comes off the line. Its microstructure includes 87% pearlite and 13% ferrite by volume, the network carbide grade is 2.5, the mechanical property difference is 64MPa, the tensile strength is 1210MPa, and the section shrinkage is 28%.
[0051] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the C-Si-Mn-Cr chemical composition, the cooling capacity of the Stelmor air-cooling line is limited, which makes it difficult to control the network carbides and obtain the troostite structure with fine lamellar spacing. When the air-cooling intensity is increased, the uniformity of the wire rod structure is not high, the mechanical properties fluctuate greatly, the obtained pearlite content is not high, and the tissue stress is high, resulting in insufficient strength and plasticity. The present invention is combined with the online molten salt isothermal quenching technology. The front-end molten salt treatment is first performed to inhibit the formation of network carbides and form a structure dominated by troostite structure with fine lamellar spacing. The rear-end molten salt cooling treatment makes the formation of quenched bainite more controllable. After isothermal tempering of troostite and quenched bainite, the uniformity of the wire rod structure can be improved, the complex phase structure of the wire rod can be regulated, and the high strength and plasticity of the wire rod can be matched.
[0052] Comparative Example 2:
[0053] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method differs from that of Example 1 in that: the heating furnace soaking temperature is controlled to be 1070°C, the furnace time is 4.5h, the initial rolling temperature is 1030°C, the final rolling temperature is 890°C, the spinning temperature is 870°C, the wire rod is treated with molten salt in the front section, and the wire rod is cooled at a cooling rate of 37°C / s; the hot-rolled complex phase wire rod is obtained after it comes off the line. Embodiment 2:
[0054] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1860MPa grade stranded wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled complex phase wire rod include: C: 0.80%, Si: 0.2%, Mn: 0.2%, Cr: 0.25%, P: 0.013%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal quenching → roller strong slow cooling → coiling, specifically:
[0055] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled plastically, and control the parameters of the heating furnace to reduce the risk of decarburization of the steel billet in the furnace. After the steel billet leaves the heating furnace, the surface oxide scale is removed by high-pressure descaling water and the billet is sent to the rolling line. The rolling line rolls the steel billet into a wire with a diameter specification of 12mm. Appropriate rolling temperature and reduction amount are selected to promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is heated up in sequence according to preheating, heating, and soaking, and the residual oxygen content in the heating furnace is controlled to be 2.3%. The hot furnace average heating temperature is 1090℃, the furnace time is 4h, the descaling water pressure after the heating furnace is 14MPa, the initial rolling temperature is 1055℃, the heavy-load finishing rolling reduction is 28%, and the final rolling temperature is 915℃; the wire-spinning process is used to turn the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The higher wire-spinning temperature ensures that the wire rods are in a high-temperature austenitized state and prevents the precipitation of network carbides, which provides favorable conditions for the subsequent formation of a larger degree of supercooling and thus refinement of the troostite lamellar spacing. Specifically: the wire-spinning temperature is controlled to be 895℃.
[0056] The online molten salt isothermal quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller to pass through the first stage salt bath tank, that is, it is subjected to the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to the pearlite phase area, inhibiting the formation of network carbides and causing part of the austenite phase to transform into a structure mainly composed of sorbite, and then conveyed by a roller to pass through the second stage salt bath tank, that is, it is subjected to the rear stage molten salt treatment, and the cooling promotes The residual austenite is transformed into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and the micro-spheroidization of some cementite sheets is promoted to regulate the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 515°C, the processing time is 40s, the molten salt circulation volume is 500t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear-stage molten salt is 459°C, the processing time is 36s, the molten salt circulation volume is 380t / h, and the molten salt temperature rise is ≤3°C.
[0057] The roller strong slow cooling process adopts the insulation cover to close, and the high temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover, so as to promote the further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 285°C at a slow cooling rate of 0.24°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0058] Comparative Example 3:
[0059] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which differs from that of Example 2 in that: the molten salt temperature of the front-stage molten salt is 490°C, the wire rod is cooled at a cooling rate of 41°C / s, and the processing time is 60s; the hot-rolled complex phase wire rod is obtained after it comes off the line.
[0060] Comparative Example 4:
[0061] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which differs from that of Example 2 in that: the molten salt temperature of the front-stage molten salt is 530°C, the wire rod is cooled at a cooling rate of 360°C / s, and the processing time is 25s; the hot-rolled complex phase wire rod is obtained after going offline. Embodiment 3:
[0062] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1860MPa grade stranded wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled complex phase wire rod include: C: 0.83%, Si: 0.4%, Mn: 0.35%, Cr: 0.15%, P: 0.012%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal quenching → roller strong slow cooling → coiling, specifically:
[0063] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled plastically, and control the parameters of the heating furnace to reduce the risk of decarburization of the steel billet in the furnace. After the steel billet leaves the heating furnace, the surface oxide scale is removed by high-pressure descaling water and the billet is sent to the rolling line. The rolling line rolls the steel billet into a wire with a diameter specification of 15mm. Appropriate rolling temperature and reduction amount are selected to promote dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is heated up in sequence according to preheating, heating, and soaking, and the residual oxygen content in the heating furnace is controlled to be 1.5%. The hot furnace soaking temperature is 1110℃, the furnace time is 3h, the descaling water pressure after the heating furnace is 17MPa, the initial rolling temperature is 1075℃, the heavy-load finishing rolling reduction is 22%, and the final rolling temperature is 925℃; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through the wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. The higher wire-spinning temperature ensures that the wire rods are in a high-temperature austenitized state and prevents the precipitation of network carbides, which provides favorable conditions for the subsequent formation of a larger degree of supercooling and thus refinement of the troostite lamellar spacing. Specifically: the wire-spinning temperature is controlled to be 905℃.
[0064] The online molten salt isothermal quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank, that is, it is subjected to the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 41°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to the pearlite phase area, inhibiting the formation of network carbides and causing part of the austenite phase to transform into a structure mainly composed of sorbite, and then conveyed by a roller through the second stage salt bath tank, that is, it is subjected to the rear stage molten salt treatment, and the cooling promotes The residual austenite is transformed into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and the micro-spheroidization of some cementite sheets is caused to occur, so as to regulate the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 508°C, the processing time is 45s, the molten salt circulation volume is 600t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear-stage molten salt is 448°C, the processing time is 40s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤3°C.
[0065] The roller strong slow cooling process adopts the insulation cover to close, and the high temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the insulation cover, so as to promote the further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 290°C at a slow cooling rate of 0.15°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0066] Comparative Example 5:
[0067] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which is different from that of Example 3 in that: the molten salt temperature of the rear-stage molten salt is 420° C., and the processing time is 60 s; and the hot-rolled complex phase wire rod is obtained after going offline.
[0068] Comparative Example 6:
[0069] A method for manufacturing a hot-rolled complex phase wire rod, the manufacturing method of which is different from that of Example 3 in that: the molten salt temperature of the rear-stage molten salt is 485° C., and the processing time is 25 s; and the hot-rolled complex phase wire rod is obtained after going offline. Embodiment 4:
[0070] A preferred embodiment of the method for manufacturing the hot-rolled complex phase 1860MPa grade stranded wire rod of the present invention, the chemical composition and mass percentage of the hot-rolled complex phase wire rod include: C: 0.84%, Si: 0.32%, Mn: 0.28%, Cr: 0.19%, P: 0.013%, S: 0.014%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal quenching → roller strong slow cooling → coiling, specifically:
[0071] The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled plastically, and control the parameters of the heating furnace to reduce the risk of decarburization of the steel billet in the furnace. After the steel billet leaves the heating furnace, the surface oxide scale is removed by high-pressure descaling water and the billet is sent to the rolling line. The rolling line rolls the steel billet into a wire with a diameter specification of 13mm. Appropriate rolling temperature and reduction amount are selected to promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace is heated up in sequence according to preheating, heating, and soaking, and the residual oxygen content in the heating furnace is controlled to be 1.3%. The furnace average heating temperature is 1120℃, the furnace time is 2.5h, the descaling water pressure after the heating furnace is 16MPa, the initial rolling temperature is 1085℃, the heavy-load finishing rolling reduction is 26%, and the final rolling temperature is 935℃; the wire-spinning process is used to make the wire rods coming out of the rolling line through the wire-spinning mechanism into wire rods, which are spread on the rollers and transported along the rollers. The higher wire-spinning temperature ensures that the wire rods are in a high-temperature austenitized state and prevents the precipitation of network carbides, which provides favorable conditions for the subsequent formation of a larger degree of supercooling and thus refinement of the troostite lamellar spacing. Specifically: the wire-spinning temperature is controlled to be 910℃.
[0072] The online molten salt isothermal quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank, that is, it is subjected to the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to the pearlite phase area, inhibiting the formation of network carbides and causing part of the austenite phase to transform into a structure mainly composed of sorbite, and then conveyed by a roller through the second stage salt bath tank, that is, it is subjected to the rear stage molten salt treatment, and the cooling promotes The residual austenite is transformed into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and the micro-spheroidization of some cementite sheets is promoted to regulate the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-stage molten salt is 520°C, the processing time is 30s, the molten salt circulation volume is 550t / h, and the molten salt temperature rise is ≤5°C; the molten salt temperature of the rear-stage molten salt is 430°C, the processing time is 30s, the molten salt circulation volume is 450t / h, and the molten salt temperature rise is ≤3°C.
[0073] The roller strong slow cooling process adopts a heat preservation cover to close, and the high-temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller, and the wire rod passing through the second section of the salt bath tank is transported by the conveying roller into the heat preservation cover, so as to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 296°C at a slow cooling rate of 0.1°C / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled complex phase wire rod product is obtained after packaging and storage.
[0074] Comparative Example 7:
[0075] A method for manufacturing a hot-rolled complex phase wire rod, which differs from Example 4 in that: the method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal quenching → air cooling, the air cooling adopts the method of opening the heat preservation cover, and conveying the wire rod through the second salt bath tank by the conveyor roller, and controlling the wire rod to have a slow cooling rate of 1.9°C / s, and obtaining the hot-rolled complex phase wire rod after it comes off the line.
[0076] The hot rolled multiphase wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were subjected to microstructure and performance tests, and the obtained comparative results are shown in Table 1 below:
[0077] Table 1. Comparison of microstructure and properties of hot rolled multiphase wire rods with different compositions and manufacturing methods
[0078]
[0079] It can be seen from the results of Examples 1 to 4 that the microstructure type of the hot-rolled multiphase wire rod of the present invention is a composite structure composed of mostly tempered troostite, a small portion of tempered bainite, and the rest being tempered ferrite and micro-spheroidized carbides. The product tensile strength can reach 1290 to 1340 MPa, the cross-sectional shrinkage rate is 41% to 46%, and the mechanical property difference is ≤30 MPa. It is suitable for use as a base material to manufacture 1860 MPa grade stranded wire, and can reduce the risk of wire breakage during drawing and braiding.
[0080] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the use of a higher spinning temperature can ensure that the wire rod is in a high-temperature austenitized state, prevent the precipitation of network carbides in the spinning stage, and is beneficial to increasing the degree of supercooling and refining the spacing between troostite lamellae. It can also reduce the restrictions on rolling temperature to improve rolling efficiency.
[0081] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the more troostite is formed and the finer the spacing between the troostite lamellae, which is beneficial to the transformation of cementite sheets into microspheres. The proportion of tempered bainite decreases, and the plasticity of the matrix increases. However, if the molten salt temperature is too low and the treatment time is too long, there will be too little residual austenite in the structure that can be transformed into quenched bainite structure, which will result in insufficient strength of the wire rod.
[0082] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature of the front-stage molten salt and the shorter the treatment time, the less troostite is formed and the greater the spacing between troostite lamellae, so that more residual austenite is left in the organization and can be transformed into quenched bainite organization, thereby increasing the proportion of tempered bainite and increasing the strength of the matrix. However, if the molten salt temperature is too high and the treatment time is too short, it will be unfavorable for the incubation of troostite, and the proportion of tempered bainite in the complex phase organization will be too high, resulting in insufficient plasticity.
[0083] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the lower the molten salt temperature of the rear-stage molten salt and the longer the treatment time, it is beneficial to promote the rapid transformation of retained austenite into quenched bainite structure, promote the toughening and softening of the structure, and micro-spheroidize some cementite sheets, thereby improving the strength and plasticity of the matrix. However, if the molten salt temperature is too low and the thermal power is insufficient, the isothermal tempering effect will be reduced, resulting in insufficient plasticity of the wire rod. If the treatment time is too long, there is a risk of precipitation and coarsening of Cr and deterioration of the strength and plasticity.
[0084] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the higher the molten salt temperature of the rear-stage molten salt and the shorter the treatment time, it is not conducive to the rapid transformation of the residual austenite into the quenched bainite structure, resulting in a decrease in the proportion of tempered bainite and a decrease in the matrix strength. However, if the molten salt temperature is too high and the proportion of tempered bainite is too low, the wire rod is prone to excessive softening, resulting in insufficient strength of the wire rod.
[0085] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the strong slow cooling treatment can continue the high temperature state of the wire rod after passing through the molten salt, promote further toughening of the wire rod structure, and improve the tempering softening effect of the wire rod.
[0086] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a hot-rolled multi-phase 1860 MPa grade stranded wire rod, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled multiphase wire rod, and the chemical composition and mass percentage of the hot-rolled multiphase wire rod include: C: 0.80%~0.84%, Si: 0.20%~0.40%, Mn: 0.20%~0.35%, Cr: 0.15%~0.25%, P≤0.014%, S≤0.014%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥895°C, it is subjected to an online molten salt isothermal quenching treatment, so that the wire rod first passes through the front section molten salt and is cooled at a cooling rate of ≥39°C / s, enters the pearlite phase region from the austenite state, so that part of the austenite is transformed into a structure mainly composed of sorbite, and then is cooled by the rear section molten salt to promote the residual The remaining austenite is transformed into quenched bainite, the isothermal tempering of troostite and quenched bainite is promoted, and part of the cementite sheets are micro-spheroidized. Finally, after strong slow cooling on a roller, a hot-rolled complex phase wire rod with a microstructure including 81% to 87% tempered troostite by volume, 7% to 12% tempered bainite by volume, and the rest being a complex phase structure composed of tempered ferrite and micro-spheroidized carbides is prepared; the molten salt temperature of the front section molten salt is 500 to 520°C, the processing time is 30 to 50s, the molten salt temperature of the rear section molten salt is 430 to 470°C, the processing time is 30 to 50s, and the strong slow cooling on the roller controls the wire rod to be cooled to below 300°C at a slow cooling rate of 0.1 to 0.3°C / s for coiling.
2. The method for manufacturing the hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 1, characterized in that: Before the rolling, the residual oxygen content in the heating furnace is controlled to be 1.3%-2.3%, the soaking temperature of the heating furnace is 1090-1120°C, the time in the furnace is 2.5-4h, and the descaling water pressure after passing through the heating furnace is 14-17MPa.
3. The method for manufacturing the hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1055-1085°C, the heavy-load finishing rolling reduction is 22%-28%, and the final rolling temperature is ≥915°C.
4. The method for manufacturing the hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 1, characterized in that: The molten salt circulation volume of the front-stage molten salt is 500-650 t / h, and the molten salt temperature rise is ≤5°C; the molten salt circulation volume of the rear-stage molten salt is 300-450 t / h, and the molten salt temperature rise is ≤3°C.
5. The method for manufacturing the hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 1, characterized in that: The roller table strong slow cooling adopts a heat preservation cover to close, and the high-temperature gas of ≥300°C above the salt bath tank during the online molten salt isothermal quenching treatment is blown to the conveying roller table, and the wire rod is conveyed by the conveying roller table into the heat preservation cover.
6. A hot-rolled multiphase 1860MPa grade stranded wire rod, characterized in that: The hot-rolled complex phase wire rod is manufactured by the method for manufacturing the hot-rolled complex phase 1860 MPa grade stranded wire rod according to any one of claims 1 to 5.
7. The hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 6, characterized in that: The interlamellar spacing of the tempered bainite is 75-115 nm, the network carbide grade of the hot-rolled multiphase wire rod is grade 0, and the mechanical property circle difference is ≤30 MPa.
8. The hot-rolled multi-phase 1860 MPa grade stranded wire rod according to claim 6, characterized in that: The hot-rolled multiphase wire rod has a diameter of 12-15 mm, a tensile strength of 1290-1340 MPa, and a cross-sectional shrinkage of 41%-46%.
Citation Information
Patent Citations
Low-manganese, high-carbon steel wire rod for high-strength steel strand and its preparation method
CN108004470B
Cold heading steel wire rod for 15.9-grade non-quenched and tempered bolt and manufacturing method of cold heading steel wire rod
CN118653094A
Hot-rolled complex-phase 1770MPa-grade steel wire rod for bridge cable and manufacturing method thereof
CN118854017A